Training teachers on the use of an augmentative and alternative communication system - Vega, Fàtima; Gràcia, Marta (Revista de Investigación en Logopedia, 2016)
This study presents the findings resulting from training a teacher, a teacher-assistant and a speechtherapist on the use of an alternative augmentative communication system (AAC) based on keyword signing (KWS), with the aim of encouraging the development of the communication skills of six pupils with intellectual and developmental disabilities (IDD) and other associated disorders, aged between 6 and 8 years old. The results show that the incorporation of keyword signing by the three participants in their interactions with the students, as well as speaking more slowly, were both beneficial. As for the students, the use of AAC was different for each of them and, in some cases, there was a slight increase in their turn taking. Continued work with the teachers to help create a “Communication Friendly Environment” would be beneficial.